2021
DOI: 10.1017/s0007114521000830
|View full text |Cite
|
Sign up to set email alerts
|

Coffee and tea consumption and the risk of glioma: a systematic review and dose–response meta-analysis

Abstract: In this systematic review and dose-response meta-analysis, we aim to assess whether coffee and tea consumption is related to the risk of glioma. We performed a systematic literature search using PubMed, Embase, Scopus, and the EuropePMC up until 1st October 2020. Exposures in this study were coffee and tea consumption. The main outcome of this study was the incidence of glioma. This study compares the association between the exposure of coffee and tea with the incidence of glioma, the results are reported in R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 38 publications
1
7
0
Order By: Relevance
“…Every extra cup of tea daily could reduce the risk of glioma by 7%, while the result of coffee was not significant (17,18). Pranata et al obtained the same conclusion through a meta-analysis (19). However, in three large prospective cohort studies in the UK and the USA, Kuan et al analyzed the effects of 15 food groups on glioma at different follow-up times, no significant effect was found (20).…”
Section: Introductionmentioning
confidence: 91%
“…Every extra cup of tea daily could reduce the risk of glioma by 7%, while the result of coffee was not significant (17,18). Pranata et al obtained the same conclusion through a meta-analysis (19). However, in three large prospective cohort studies in the UK and the USA, Kuan et al analyzed the effects of 15 food groups on glioma at different follow-up times, no significant effect was found (20).…”
Section: Introductionmentioning
confidence: 91%
“…A meta-analysis of 12 studies comprising 1,960,731 participants along with 2987 glioma cases showed that every single cup of tea or coffee per day reduces the risk of glioma to 3%. Presence of antioxidants especially polyphenols in tea or coffee may contribute to the overall chemopreventive effect against glioma [239]. Selenium is an important micronutrient with antioxidant capacity.…”
Section: Protective Roles Of Antioxidant-rich Diet In Brain Tumorsmentioning
confidence: 99%
“…Meta-regression analysis showed that higher tea consumption was related to a reduced glioma risk (RR = 0.84, 95% CI = 0.71∼0.98, p = 0.030), and sensitivity study through removing case-control studies revealed that more consumption of tea was associated with lower risk of glioma (RR = 0.81, 95% CI = 0.70∼0.93, p = 0.004). Daily 1 cup of tea reduced the glioma risk by 3% (RR = 0.97, 95% CI = 0.94∼1.00, p = 0.048) ( 39 ).…”
Section: Epidemiological Evidence Of Anticarcinogenic Effects Of Tea ...mentioning
confidence: 99%